Production of Probiotics from Streptomyces sp. Associated with Fresh water Fish and its Growth Evaluation on Xiphorous helleri - Suguna, S (International Journal of Pharmaceutical & Biological Archive, 2012)
Production of Probiotics from Streptomyces sp. Associated with Fresh water Fish and its Growth Evaluation on Xiphorous helleri